(untitled) (FUDMA JOURNAL OF SCIENCES, 2022)
Cochlospermum tinctorium root powder (Kwata) is commonly used as spice in foods and for medicinal purposes in West African sub-region. This research evaluated the rate of contamination of C. tinctorium root powder with aflatoxigenic fungi and aflatoxins. Kwata samples obtained from different sellers in Sokoto market were analyzed for presence of fungi using standard mycological methods. Aflatoxins and their concentrations in the kwata were also evaluated using EnzymeLinked Immunosorbent Assay (ELISA). The total aflatoxin concentrations of the different Kwata samples ranged from 125 to 580 ppb while aflatoxin B1 concentrations in the samples were found to be 35.5 ppb, 24.5 ppb, 32 ppb, 23.8 ppb and 45 ppb all of which are above the limits (20 ppb for adult food and 0 ppb for infant food) stipulated by regulatory bodies in Nigeria. The Aspergillus species isolated and their percentage occurrences in Kwata samples were Aspergillus niger (50% in sample A and above 25% in other samples), Aspergillus flavus (50% in sample A and 25% in other samples), Aspergillus fumigatus (33% in samples B and E and 20% in other samples). In conclusion, this study revealed high contamination of Kwata sold within Sokoto metropolis with Aspergilus species and aflatoxins, the cummulative effect of which may cause serious public health problems in populations that use this preparation in soup.